2009
DOI: 10.1063/1.3193725
|View full text |Cite
|
Sign up to set email alerts
|

Forced reptation revealed by chain pull-out simulations

Abstract: We report computation results obtained from extensive molecular dynamics simulations of tensile disentanglement of connector chains placed at the interface between two polymer bulks. Each polymer chain (either belonging to the bulks or being a connector) is treated as a sequence of beads interconnected by springs, using a coarse-grained representation based on the Kremer–Grest model, extended to account for stiffness along the chain backbone. Forced reptation of the connectors was observed during their disenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Harnau et al 18) concluded that the deviation is due to the chain rigidity (CR) from the atomistic molecular simulations for polyethylenes, for which the molecular weight is larger than that used by Paul et al 13) . A similar discussion has been made for beadspring chains by Bulacu and van der Giessen 19) . Other possible mechanisms are the excluded volume interactions (EVI) and the hydrodynamic interactions (HI).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Harnau et al 18) concluded that the deviation is due to the chain rigidity (CR) from the atomistic molecular simulations for polyethylenes, for which the molecular weight is larger than that used by Paul et al 13) . A similar discussion has been made for beadspring chains by Bulacu and van der Giessen 19) . Other possible mechanisms are the excluded volume interactions (EVI) and the hydrodynamic interactions (HI).…”
Section: Introductionsupporting
confidence: 56%
“…Indeed, the earlier results 17) have shown that for p < 4 the eigenfunction is fairly close to the sinusoidal function. It has also been noted that Bulacu and van der Giessen 19) have utilized the sinusoidal eigenfunction to discuss the effect of chain stiffness on the normal modes for bead-spring simulations even for larger values of p. Hirao et al 35) have obtained the exact eigenfunction numerically using the variational method 36) for single Kremer-Grest chain floating in vacuum to report that the obtained function is virtually identical to sinusoidal function for p ≤ 4. Hagita et al 37) have applied the variational method to obtain the relaxation time for normal modes for polymer melts simulated via dynamic Monte Carlo.…”
Section: Resultsmentioning
confidence: 99%
“…where n and m denote the monomer indices and α and β denote the three spatial directions. An important observable frequently discussed in the context of simulations of polymeric systems and the elucidation of the quality of the Rouse model is the mean square displacement (MSD) [3][4][5][6] . Naturally, the MSD of the monomers of a polymer chain shows subdiffusive motion on a time scale below the longest relaxation time τ R due to the chain connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…We implement intramolecular barriers by means of the bending, V B , and torsion potential, V T , proposed in Ref. [12] (see discussion there), which are defined for each…”
mentioning
confidence: 99%